A Flexible Energy Harvester from an Organic Ferroelectric Ammonium Salt. Issue 24 (10th November 2021) - Gupta, Rishabh; Sahoo, Supriya; Deswal, Swati; Kothavade, Premkumar; Dixit, Prashant; Zaręba, Jan K.; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy
Abstract: Organic ferroelectrics due to their low cost, easy preparation, light weight, high flexibility and phase stability are gaining tremendous attention in the field of portable electronics. In this work, we report the synthesis, structure and ferroelectric behavior of a two‐component ammonium salt 2, containing a bulky [Bn(4‐BrBn)NMe2 ] + (Bn=benzyl and 4‐BrBn=4‐bromobenzyl) cation and tetrahedral (BF4 ) − anion. The structural analysis revealed the presence of rich non‐classical C−H⋅⋅⋅F and C−H⋅⋅⋅Br interactions in this molecule that were quantified by Hirshfeld surface analysis. The polarization ( P ) vs. electric field ( E ) hysteresis loop measurements on 2 gave a remnant polarization ( Pr ) of 14.4 μC cm −2 at room temperature. Flexible polymer composites with various (5, 10, 15 and 20) weight percentages (wt%) of 2 in thermoplastic polyurethane (TPU) were prepared and tested for mechanical energy harvesting applications. A notable peak‐to‐peak output voltage of 20 V, maximum current density of 1.1 μA cm −2 and power density of 21.1 μW cm −2 were recorded for the 15 wt% 2 ‐TPU composite device. Furthermore, the voltage output generated from this device was utilized to rapidly charge a 100 μF capacitor, with stored energies and measured charges of 156 μJ and 121.6 μC, respectively. Abstract : A ferroelectric ammonium salt containing mixed benzyl substituents on the nitrogen atom and tetrafluoroborate anion was synthesized and utilized as all‐organic composite device for piezoelectric energy harvesting applications.